UPAYA PENINGKATAN PENDAPATAN MELALUI PEMBERDAYAAN MASYARAKAT DI DESA MARIAH HOMBANG KECAMATAN HUTA BAYU RAJA KABUPATEN SIMALUNGUN - Henry Dunan Henry Dunan Pardede; Calen Calen (Politeknik Bisnis Indonesia, 2018)
This study aims to find out how efforts that can increase the income of the community through empowerment for the village community Mariah Hombang Huta Bayu Raja district. The problem of this research is to know what business needs to be done to increase people's income by utilizing spare time to increase the income of farmers and their families. Various efforts that can be done are: 1) Distributors of community production by involving the community as a social entrepreneur, 2) Empowering the community as human resources by conducting education and training, 3) Moving social action with a container of village organizations that can provide motivation for the spirit of coorporation. With the program by utilizing the Village Fund is expected to empower people in increasing revenue can be achieved and provide motivation for other villagers. Government programs in fostering village financial institutions or BUMDes will be achieved if the people of Mariah Hombang village get the support of local government of Simalungun regency in terms of capital and human resources improvement.